13 number ones [compact disc] - Keith, Toby (Show Dog Nashville, 2024)
The familiar maxim of the triple threat, singer, songwriter, entertainer, didn't begin to cover it for Toby Keith, one of the most prolific self-directed creative forces in country's modern era. The new compilation features thirteen of his biggest and most beloved country singles released between 1993 and 2005. The songs selected were always performed live by Keith. Nearly all the songs on are performed during the Toby Keith: American Icon All Star Celebration concert and were consistently part of his concert setlists. Keith amassed 42 Top 10 hits, 33 No. 1s and 44 million albums sold. Among his many accomplishments, the New York-based, all-genre Songwriters Hall of Fame (2015), the National Medal of Arts (2021), the Nashville Songwriters Hall of Fame (2021), and BMI Icon (2022) were his most treasured. He was elected to the Country Music Hall of Fame shortly before his passing in February 2024.